BEBERAPA FAKTOR YANG MEMPENGARUHI PENCAPAIAN TARGET CDR OLEH KADER TB ‘AISYIYAH DALAM PENEMUAN KASUS TB DI KOTA SEMARANG - Madania Shalsabila Savitri; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Tuberculosis (TB) is one of the infectious infections that need cross-sectoral cooperation and community organization in its eradication efforts. The ‘Aisyiyah organization took the role of forming the cadres of TB Care' ‘Aisyiyah Community who are expected to actively tackle the spread of TB. This study aims to determine several factors that influence the achievement of CDR target by TB ‘Aisyiyah Cadres within TB case finding in Semarang City. This research was a quantitative research with a cross-sectional approach by using total sampling technique which was obtained 58 TB cadres as the sample of ‘Aisyiyah Semarang Organization. Data collection was conducted through an interview with the questionnaire. Data analysis was conducted using univariate and bivariate. The result of the research found that there were 36 (62,4%) active cadres in TB case discovery and 22 (37,6%) cadres were less active in TB case discovery. Most of the respondents were belong in the productive age category that was vulnerable between 20-60 years (96.5%) and last educated of high school/equivalent (69%).The results showed that dependent variable related to Knowledge (p = 0,007), Training (p = 0,025), Attitude (p = 0,005), Motivation (p = 0,005), Personality (p = 0,003), Perception (p = 0,012), Decision Making (p = 0,018), Performance (p = 0,006), Work Design (p = 0,032), and Emotion (p = 0,041).This study concludes that the achievement of CDR target by TB ‘Aisyiyah cadres within TB case discovery has already well. However, there still found less active cadres within TB case discovery. Therefore, the role of the organization and the government in the empowerment of cadres is needed in order to make case discovery goes according to the specified target.